A tale of two basins: Juxtaposition of the Ediacaran fossil-bearing St. John’s Basin against the Ediacaran glaciovolcanic Bonavista Basin on the Bonavista Peninsula, Avalon Zone, Newfoundland - Mills, Andrea J.; Normore, Leon; Gomez, Nicolas; Dunning, Gregory R.; Lowe, David G. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2024)
The Musgravetown Supergroup (MSG) of the Bonavista Basin is the central unit of Neoproterozoic strata on the Bonavista Peninsula, Avalon Zone, northeastern Newfoundland. In west Bonavista, the deep-marine ca. 620–600 Ma Connecting Point Group (CPG) is unconformably overlain by the ca. 600–540 Ma terrestrial to shallow-marine volcanic-sedimentary MSG, but fault-bounded to the east by the Indian Arm Fault. On eastern Bonavista Peninsula, the Spillars Cove Fault separates the MSG from St. John’s Basin rocks, correlative with Ediacaran strata of the Avalon Peninsula (Conception, St. John’s and Signal Hill groups) as corroborated by a U–Pb age of ca. 566 Ma. Age constraints presented here confirm the regional significance of the Spillars Cove Fault that bounds temporally and stratigraphically distinct strata.Magmatic rocks of the Bull Arm Group (basal MSG) were emplaced during protracted regional extension. The onset is marked by eruption of ca. 600 Ma calc-alkaline basalt and coeval deposition of cobble conglomerate on the ca. 605–600 Ma CPG-MSG unconformity on western Bonavista Peninsula. Extension continued through extrusion of ca. 592 Ma tuffs and bimodal volcanics of the Plate Cove volcanic belt east of the Indian Arm Fault. The belt is overlain to the east by the mainly clastic Rocky Harbour Group. Its tuffs and peperite, locally dated at ca. 585 and 576 Ma, respectively, bracket the ca. 580 Ma Trinity diamictite—a shallow-marine equivalent of the deep-marine Gaskiers Formation of the St. John’s Basin on Avalon Peninsula. Small-volume alkaline basalts below and above the Trinity diamictite provide a clear spatio-temporal link between glaciation and extensional magmatism. Strata below the Trinity diamictite display features reflecting a glaciogenic origin and increase the thickness and areal extent of Ediacaran Gaskiers glacial deposits. The Gaskiers glaciation likely lasted for several million years and was coeval with ca. 600–576 Ma extensional magmatism within proto-West Avalonia or along its margin.